Faktor Internal Dan Eksternal Yang Mempengaruhi Keberhasilan Menyusui Pada Ibu Post Sectio Caesarea Di RSUD Dr. Saiful Anwar Malang - Poppy Poppy Indah Y; Wenny Rahmawati; Jiarti Kusbandiyah (LPPM Widyagama Husada Malang, 2026)
Yanuarti, Poppy Indah. 2025. External and Internal Factors of Post-Cesarean Section Patients Affecting Breastfeeding Success at Dr. Saiful Anwar Regional General Hospital Malang. Undergraduate Program in Midwifery Science. Widyagama Husada School of Health Sciences Malang. Supervisors: I. Bd. Wenny Rahmawati, S.Keb., M.Keb., II. Jiarti Kusbandiyah, S.SiT., M.Kes. Breastfeeding rates in Indonesia have decreased significantly in recent years, prompting UNICEF and WHO to call for greater efforts to protect, promote, and support breastfeeding practices. A preliminary study at Dr. Saiful Anwar Regional General Hospital Malang revealed that 68.5% of mothers breastfed their infants from days 1-5 post-cesarean section. Post-cesarean section mothers who did not breastfeed their infants until the postnatal control visit accounted for 15.1%, with reasons including insufficient milk production and mothers undergoing medical treatment. The remaining 16.2% of mothers did not breastfeed due to infant mortality. The aim of this study was to analyze the external and internal factors of post-cesarean section patients affecting breastfeeding success at Dr. Saiful Anwar Regional General Hospital Malang in 2025. This study employed an observational analytical research design with a cross-sectional approach. The research utilized questionnaire sheets as the research instrument and employed accidental sampling with 62 respondents during November-December 2024. Data processing in this study used computerized techniques assisted by SPSS and employed Chi-Square formula. Based on the research conducted to analyze external factors in post-cesarean section patients among 62 respondents, it was found that respondents who received family support and achieved successful breastfeeding accounted for 45.7%, which was higher compared to those who received support but did not succeed in breastfeeding (37.0%). The Chi-Square statistical test showed a p-value of 0.01, indicating statistical significance (p-value <0.05). Regarding internal and external factors in post-cesarean section patients among 62 respondents, it was found that respondents who produced abundant breast milk and succeeded in breastfeeding accounted for 54.2%, higher than respondents who produced abundant milk but did not succeed in breastfeeding (45.8%). The Chi-Square statistical test showed a p-value of 0.04, indicating statistical significance (p-value <0.05). Healthcare professionals should enhance services by motivating and educating mothers on exclusive breastfeeding, implementing rooming-in practices to enable mothers to easily observe, care for, and breastfeed their infants, and evaluate breastfeeding success at home with follow-up education. References : 27 References (2014–2024) Keywords : Anxiety,Post-Cesarean Section, Family Support, Hospital Support, Breastfeeding Success, Breastfeeding, Surgical Wound Pain, Breast Milk Production, Post Cesarean Section.